2022
DOI: 10.3389/fgene.2022.808542
|View full text |Cite
|
Sign up to set email alerts
|

Association of FLG mutation with tumor mutation load and clinical outcomes in patients with gastric cancer

Abstract: Background: Stomach adenocarcinoma (STAD) is one of the most frequently diagnosed cancers in the world with a poor prognosis due to genetic heterogeneity. The present study aimed to explore potential prognostic predictors and therapeutic targets that can be used for STAD treatment.Methods: We collected relevant data of STAD patients from the Cancer Genome Atlas (TCGA), including somatic mutation, transcriptome, and survival data. We performed a series of analyses such as tumor mutational burden (TMB), immune i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…We also found that FLG is highly mutated and has a signi cant effect on GC prognosis and immune in ltration, including CNV variants and missense mutations. It was partially in concordance with previously published studies [33][34] . In addition, we know that immune cells play a key regulatory role in tumorigenesis and development [35] .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We also found that FLG is highly mutated and has a signi cant effect on GC prognosis and immune in ltration, including CNV variants and missense mutations. It was partially in concordance with previously published studies [33][34] . In addition, we know that immune cells play a key regulatory role in tumorigenesis and development [35] .…”
Section: Discussionsupporting
confidence: 93%
“…Fu Yicheng indicated that GC patients carrying FLG mutations have signi cantly higher OS and DFS [33] .…”
Section: Discussionmentioning
confidence: 99%
“…FLG also had a lower proportion of mutations in the high-risk group. It has been reported that the FLG mutant group showed a higher mutation load and immunogenicity in gastric cancer, resulting in increased sensitivity of gastric cancer to 24 chemotherapy agents ( 44 ). Our data also showed an association between a higher proportion of FLG mutations and a better response to STAD therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In a prior study, FLG was found to have a higher mutation frequency in prostate cancer and to be associated with an increase in TMB, up-regulation of aberrant immune responses in tumors, and cancer growth than the wild type ( 34 ). The recently published data showed that the FLG-mutant group (FLG-MT) had a greater mutation load and immunogenicity, suggesting that the gene mutation may be a preventative measure in gastric tumor ( 35 ). Other early results suggested that certain atopy-related variations, including the FLG gene may be linked to an increased risk of pancreatic cancer ( 36 ).…”
Section: Discussionmentioning
confidence: 99%